Part C early intervention utilization in preterm infants: Opportunity for referral from a NICU follow-up clinic. (June 2016) - Greene, Michelle; Patra, Kousiki
Highlights: CFC enrollment is common (40–80%) among preterm infants seen in a NICU clinic. However, 14–28% of preterm infants required referral to CFC from the NICU clinic. Up to 28% of ELBW infants, who are auto-eligible for CFC, required CFC referral. Social variables were associated with need for CFC referral from the NICU clinic. NICU clinics play an important role in identifying unmet CFC/EI needs. Abstract: Objective: Early Intervention (EI) services promote development for preterm infants. In the state of Illinois, Child and Family Connections (CFC) is the intake agency that determines qualification for EI services. In Illinois, all extremely low birth weight (ELBW) infants are eligible for and referred to CFC at discharge from the Neonatal Intensive Care Unit (NICU). This study investigated: (1) patterns of CFC and EI enrollment, and; (2) predictors of CFC enrollment, need for CFC referral, and high EI therapy use among preterm infants seen in a NICU follow-up clinic. Methods: 405 preterm infants, including 169 ELBW infants, were seen in a NICU follow-up clinic at 4-, 8- and 20-months corrected age. CFC/EI data were collected at each visit. Multiple regression analyses adjusted for the effect of medical, sociodemographic and neurodevelopmental risk factors on CFC/EI outcome. Results: Despite the high rate of EI utilization and routine care by primary pediatricians, up to 28% of ELBW infants required a CFC referral from a NICU follow-up clinic. Medical and neurodevelopmental risk factors were associated with CFC enrollment while medical, sociodemographic and neurodevelopmental risk factors were associated with need for CFC referral. Conclusion: NICU follow-up clinics facilitate appropriate CFC/EI services for preterm infants.